Hamba Tuhan dan Bacaannya (II Timotius 4:13) - Lukito, Daniel Lucas (Seminari Alkitab Asia Tenggara, 2000)
Naskah khotbah
Keywords: Bible. Timothy, 2nd, IV,13 -- Sermons.; Christians -- Books and reading.